Catalytic Asymmetric Alkylation of Acylsilanes1. Issue 10 (17th November 2014) - Rong, Jiawei; Oost, Rik; Desmarchelier, Alaric; Minnaard, Adriaan J.; Harutyunyan, Syuzanna R.
Abstract The highly enantioselective addition of Grignard reagents to acylsilanes is catalyzed by copper diphosphine complexes. This transformation affords α‐silylated tertiary alcohols in up to 97 % yield and 98:2 enantiomeric ratio. The competing Meerwein–Ponndorf–Verley reduction is suppressed by the use of a mixture of Lewis acid additives. The chiral catalyst can be recovered as a copper complex and used repeatedly without any loss of catalytic activity.